Modernity, postmodernity, and an evolving spirituality - Phillips, Timothy (Review and expositor, 2018)
This article comes from chapter 1 of a DMin dissertation entitled "Evolutionary Theology and Revolutionary Worship," which can be found in the Library of the Graduate Theological Union in Berkeley, CA. The dissertation uses evolution as a metaphor for its understanding of God, through which the modern mainline Church can claim its unique spiritual identity and find connections with evangelicals who increasingly see evolution as an apt description of their own spiritual experience., In order to transform the conversation about worship from "worship wars" toward a priority for authenticity, this article makes two basic claims related to the perceived decline of the modern mainline Church: (i) the emerging evangelical churches seek to embrace the culture of postmodernity while rejecting the postmodern philosophical stance; and (ii) while the values of the modern mainline Church may resonate with postmodernity, it is often stuck in its own culture of modernity.